Psychological Effects of Economic Recession and Unemployment - Kapuvári, Virág (European Journal of Mental Health, 2011)
The aim of this study is to explore research projects to demonstrate some of the problems connected with health consequences of unemployment. There is a growing body of evidence that unemployment can influence physical and mental health. This review essay focuses on health consequences of economic recession and unemployment. The author explores some important Hungarian events which serve as a historical context of the whole topic to later analyse the mental effects of unemployment. Concerning the mental consequences of this phenomenon, anxiety, depression, and low self-esteem often occur among unemployed people. Learned helplessness is well known in the literature as well. The author makes an attempt to interpret the topics above and the stages unemployed people undergo. Numerous psychological theories of unemployment are known such as frustration theory, life-span developmental theory, deprivation theory, agency restriction theory, and the vitamin model, which try to explain the importance of work in people’s life. In this paper the author tries to emphasise a possibility of the crisis originating in the economic recession and affecting not only individual life but also the whole society.